Penguatan Pendidikan Karakter melalui Pelatihan Penulisan Subtema Buku Let’s Respect Each Other dengan Kecerdasan Buatan - Wardani, Agista Nidya; Maro, Rahmawati Khadijah (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2025)
This community service program enhances character education at TK Aisyiyah 5 Mataram by adding a sub-theme on respecting teachers to Let’s Respect Each Other: A Storytelling Book of Character Building. Originally developed in 2020, the book focused on respect within family and peer relationships; the new sub-theme broadens its scope to reinforce moral values in school settings while supporting early English literacy. Through collaboration with teachers at TK Aisyiyah 5 Mataram who face challenges due to limited teaching resources that effectively convey character values in an engaging way, and by utilizing AI-based storytelling tools, this program optimizes language use and structures narratives effectively. By integrating AI technology and teacher feedback, the revised book remains engaging, relevant, and effective in fostering character development and literacy skills in children.